UTILIZATION OF CROSS-SECTION DIGITIZATION FROM 2D GEOELECTRIC RESULTS TO VISUALIZE THE SHAPE OF THE SAUNG CAVE CAVITY AS A GEOEDUCATIONAL POTENTIAL - Aminy, Ika Umratul Asni; Syamsuddin, Syamsuddin; Minardi, Suhayat; Inayah, Rahmatun; Jayatri, Adella Ulyandana; Izyatin, Nazla (Universitas Nusa Cendana, 2025)
This study was conducted to detect and visualize the presence of cave cavities in the Saung Penggembur Cave area, Central Lombok, to support efforts to develop the area as a geo-educational facility. The method used was 2D resistivity geophysics with a Wenner configuration on four measurement lines. The data obtained were processed using Res2dinv software to produce subsurface cross-sections. The cross-section results from the four measurement lines showed continuously increasing values with increasing depth. These results were then digitized to visualize the cave's shape based on the obtained resistivity values. Cave cavities were assumed to have high resistivity values ranging from 725 to 1000 Ωm. These values were found at a depth of 2.5 m, or even deeper. These results indicate that the presence of cave cavities varies at each point. This condition is supported by field observations showing the presence of a hole above the surface. These results are interpreted as an indication of the presence of cavities or cave passages. This study provides an initial overview of subsurface geological conditions and demonstrates the efficacy of the 2D geophysical method in non-invasively identifying hollow zones. These findings are important for supporting further geological exploration, the preservation of karst areas, and the development of geoeducation's potential as a natural laboratory.